1996
DOI: 10.1007/bf02456135
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of OspA and OspC among cerebrospinal fluid isolates ofBorrelia burgdorferi sensu lato from patients with neuroborreliosis in Germany

Abstract: Neuroborreliosis is the most frequent manifestation of the second stage of Lyme borreliosis in Europe. However, only few isolates from the cerebrospinal fluid (CSF) have been characterized with controversial results. A large panel of 36 CSF isolates isolated over a 10-year period in Munich has now been analyzed for their OspA and OspC type, resulting in at least eight different types, respectively. Representatives of the different types cultivated from CSF in Munich have also been isolated from other geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(34 citation statements)
references
References 45 publications
4
30
0
Order By: Relevance
“…One obstacle to the general applicability of this therapeutic treatment appears to be the well documented heterogeneity of OspC among members of the species B. burgdorferi sensu lato (36)(37)(38). Evidence indicates that the majority of European and North American B. burgdorferi isolates contain the OspC gene and also express the protein (38,39). In addition, it has been shown that polyclonal anti-OspC IS generated in response to one strain of B. burgdorferi crossreacted with the majority of heterologous isolates analyzed (refs.…”
Section: Discussionmentioning
confidence: 99%
“…One obstacle to the general applicability of this therapeutic treatment appears to be the well documented heterogeneity of OspC among members of the species B. burgdorferi sensu lato (36)(37)(38). Evidence indicates that the majority of European and North American B. burgdorferi isolates contain the OspC gene and also express the protein (38,39). In addition, it has been shown that polyclonal anti-OspC IS generated in response to one strain of B. burgdorferi crossreacted with the majority of heterologous isolates analyzed (refs.…”
Section: Discussionmentioning
confidence: 99%
“…The use of genome fingerprinting and other methods soon showed that the bacteria were highly diverse and in fact represented a species complex (Liveris et al, 1995; Marconi and Garon, 1992; Mathiesen et al, 1997; Postic et al, 1994; Wilske et al, 1991). Phenotypic typing tools were developed to reveal intraspecific diversity which included serotyping or multilocus enzyme electrophoresis (MLEE) (Boerlin et al, 1992; Wilske et al, 1991; Wilske et al, 1996; Wilske et al, 1995; Wilske et al, 1993). This topic is reviewed excellently by Wang and co-authors (Wang et al, 1999b) and here we concentrate on single and multilocus sequence analyses.…”
Section: Typing Tools For the Lb Group Of Spirochetesmentioning
confidence: 99%
“…Many different genes and loci have been targeted in studies depending on the level of variation and the discriminatory power required and which species were being investigated. These included intergenic spacer (IGS) regions, the rrs (16S rRNA) locus, the plasmid located genes encoding the outer surface proteins A and C ( ospA , ospC ), decorin-binding protein A ( dbpA ), the chromosomally located housekeeping genes recombinase A ( recA ), groEL , hbb or flagellin B ( flaB ) (Casati et al, 2004; Dykhuizen and Baranton, 2001; Fukunaga et al, 1996c; Liveris et al, 1995; Marconi et al, 1995; Michel et al, 2004; Park et al, 2004; Postic et al, 1994; Schulte-Spechtel et al, 2006; Valsangiacomo et al, 1997; Will et al, 1995; Wilske et al, 1996). …”
Section: Typing Tools For the Lb Group Of Spirochetesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that R. akari, R. conorii and R. sibirica are highly lethal for C3H/HeJ mice, but R. rickettsii and R. australis are not (Eisemann et al, 1984). R. helvetica did not show any pathogenic effect on Swiss mice, guinea pigs or domestic rabbits (Hajem et al, 2009 (Baranton et al, 1992;Canica et al, 1993;Wilske et al, 1996;Wang et al, 1997;Richter et al, 2006;Margos et al, 2009Margos et al, , 2013Hubálek et al, 2011). Rodents are the most important reservoir hosts for B.afzelii, B. burgdorferi s.s., B. spielmanii and B. bavariensis (Kurtenbach et al, 1998;Huegli et al, 2002;Richter et al, 2006).…”
Section: Resultsmentioning
confidence: 98%